Biogeographical implications of a new mouse-sized fossil bandicoot (Marsupialia: Peramelemorphia) occupying a dasyurid-like ecological niche across Australia - Gurovich, Yamila (2013)
We describe Bulungu palara gen. et sp. nov., a new fossil peramelemorphian (bandicoot), based on a single well-preserved skull and additional dental specimens from Late Oligocene to Middle Miocene (Faunal Zones A–C) limestone deposits at the Riversleigh World Heritage Property, Queensland, and two dental specimens from the Early–Middle Miocene Kutjamarpu Local Fauna, South Australia. This is the first fossil peramelemorphian species to be reported from more than a single fossil fauna, with its inferred distribution extending from north-western Queensland (modern latitude ∼19◦S) to north- eastern South Australia (modern latitude ∼28◦S). The presence of Bulungu palara in Riversleigh Faunal Zones A, B and C and in the Kutjamarpu Local Fauna supports the current interpretation that these faunas span similar ages, namely Late Oligocene–Middle Miocene. Phylogenetic analyses of an expanded 74 morphological character dataset using maximum parsimony and Bayesian approaches, both with and without a molecular scaffold, consistently place Bulungu and the Oligo-Miocene forms Galadi and Yarala outside crown-group Peramelemorphia. These analyses also fail to support a close relationship between the Pliocene Ischnodon australis (previously considered the oldest known representative of the extant peramelemorphian family Thylacomyidae) and the modern thylacomyid genus Macrotis. With an estimated body mass of ∼130 g, Bulungu palara is smaller than any known Recent bandicoot from Australia, although some modern New Guinean species are similar in size. The small size and craniodental morphology of B. palara suggest that it was predominantly or exclusively insectivorous, perhaps ecologically similar to small New Guinean dasyurids such as Murexechinus melanurus. Together with the small-bodied (< 100 g), insectivorous Yarala burchfieldi and large-bodied (∼900 g), faunivorous Galadi speciosus, Bulungu palara demonstrates that Oligo-Miocene Australian peramelemorphians filled ecological niches that today are mostly occupied by dasyurids, and that a major faunal turnover event occurred at some point after the Middle Miocene.